Melasma removal using Q-Switched Neodymium-doped Yttrium Aluminium Garnet laser toning and high-intensity focussed ultrasound - Shahad Abdulhadi; Mustafa Salih Al Mousawi; Wissam Majeed Kattoof (Journal of the Pakistan Medical Association)
Objective: To evaluate the effectiveness of combining high-intensity focussed ultrasound and a Q-switched neodymium-doped yttrium aluminium garnet 1064nm low-fluence toning laser in the treatment of melasma.